IJTIHAD DALAM INSTITUSI FATWA DI MALAYSIA: SATU ANALISIS - Abdul Rahim, Rahimin Affandi (Jurnal Syariah, 2009)
This article will focus on perception and application of ijtihad in the perspective of the Malaysian Institution of Fatwa. The discussion is divided into three sections: First, the introduction of the study. Second, the significance of ijtihad in the historical development of Islamic Law, Third, attempt to strengthen the utilization of ijtihad. In the third section, it will be further divided into two subdivisions: First, rejuvenate professionalism by the mufti profession, Second, strenghten Syariah role in the Malaysian Institution of Fatwa.